Helping Teens Answer the Question "Who Am I?": Moral Development in Adolescents - Sally Moore; Rosemary V. Barnett (EDIS)
FCS-2275, a 3-page fact sheet by Rosemary V. Barnett and Sally Moore, is fourth in the Helping Teens Answer the Question “Who Am I?” series. It focuses on the moral development that adolescents experience between the ages of 10 and 17 and how parents and agents can help youths develop their identity as moral beings. Includes references. Published by the UF Department of Family Youth and Community Sciences, February 2009.